2005
DOI: 10.1007/s10551-004-6711-z
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Ethical Effects in Budgeting Systems: A Comparison of U.S. and Chinese Managers

Abstract: This study developed and tested a model of culture's effect on budgeting systems, and hypothesized that system variables and reactions to them are influenced by culture-specific work-related and ethical values. Most organizational and behavioral views of budgeting fail to acknowledge the ethical components of the problem, and have largely ignored the role of culture in shaping organizational and individual values. Cross-cultural differences in reactions to system design variables, and in the behaviors motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 42 publications
0
56
0
2
Order By: Relevance
“…These studies suggest that, in general, idealism is associated with firm moral convictions, whereas relativism suggests ethical leniency. Douglas and Wier (2005), for example, found that idealism was negatively related to questionable budgetary practices (slack creation behavior), but relativism was positively correlated with such practices. Tsai and Shih (2005) report that managers who were more idealistic reported feeling greater role conflict, whereas increases in relativism went hand-in-hand with reduced conflict.…”
Section: Ethics Across Culturesmentioning
confidence: 99%
“…These studies suggest that, in general, idealism is associated with firm moral convictions, whereas relativism suggests ethical leniency. Douglas and Wier (2005), for example, found that idealism was negatively related to questionable budgetary practices (slack creation behavior), but relativism was positively correlated with such practices. Tsai and Shih (2005) report that managers who were more idealistic reported feeling greater role conflict, whereas increases in relativism went hand-in-hand with reduced conflict.…”
Section: Ethics Across Culturesmentioning
confidence: 99%
“…Hofstede"s four dimensions have scores for Arabic countries in general, and for Libya in particular as well as for Anglo-American countries (USA, UK, Canada, and Australia) which aids the comparisons. Another reason for choosing Hofstede"s model is that many authors have used Hofstede"s model to study the influence of culture on budgeting processes (Douglas et al 2007, Douglas & Wier 2005, Ueno & Wu 1993, Yee et al 2008). …”
Section: Research Questionmentioning
confidence: 99%
“…Douglas and Wier (2005, p. 163) also state that "Hofstede"s Power Distance and Individualism are expected to influence organizational choices in budgetary system design". Douglas and Wier (2005) argue that subordinates in low power distance cultures are involved in planning and decision making (Douglas & Wier 2005, O'Connor 1995. In low power distance cultures, inferiors see their superiors as equal and employees expect their superiors to consult them and vice versa.…”
Section: Budgetary Participationmentioning
confidence: 99%
See 2 more Smart Citations